MonTI 2019
DOI: 10.6035/monti.2019.ne5.4
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura y tratamiento informativo de la persona que traduce en la prensa

Abstract: Este obra está bajo una licencia de Creative Commons Reconocimiento 4.0 Internacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Despite being a largely invisible phenomenon in the public sphere, translation often makes news headlines. In a recent study on the representation of 'translators' in news, Luna Alonso (2019) observed that, along with topics that have been more extensively covered, including the deprofessionalisation of the sector and important achievements related to literary translation, the growth of new translation technologies has regularly become newsworthy in very recent times. While Luna Alonso's conclusions are indicative of the democratisation of free machine translation in general, more recent headlines hint at the visible use of machine translation in the newsrooms of a 'convergent' media sector where cross-media content needs to be quickly distributed in a multiplicity of formats and on a variety of (social media) platforms (Davier & Conway, 2019).…”
Section: A Paradigm Shift Underway? Signs Of Change In Translational Behaviour In News Productionmentioning
confidence: 99%
“…Despite being a largely invisible phenomenon in the public sphere, translation often makes news headlines. In a recent study on the representation of 'translators' in news, Luna Alonso (2019) observed that, along with topics that have been more extensively covered, including the deprofessionalisation of the sector and important achievements related to literary translation, the growth of new translation technologies has regularly become newsworthy in very recent times. While Luna Alonso's conclusions are indicative of the democratisation of free machine translation in general, more recent headlines hint at the visible use of machine translation in the newsrooms of a 'convergent' media sector where cross-media content needs to be quickly distributed in a multiplicity of formats and on a variety of (social media) platforms (Davier & Conway, 2019).…”
Section: A Paradigm Shift Underway? Signs Of Change In Translational Behaviour In News Productionmentioning
confidence: 99%
“…En traducción periodística, al contrario que en la traducción de títulos científicos altamente especializados, la literatura sobre la traducción de titulares es copiosa (Reque de Coulon, 2002;Hernández Guerrero, 2004;Andújar Moreno, 2006;Aştirbei, 2011;Vella Ramírez y Martínez López, 2012;Al Duweiri y Baya Essayahi, 2016;Luna Alonso, 2019; entre otros). Hernández Guerrero ( 2004) estudia la traducción de los titulares del francés al español y pone de manifiesto que los textos periodísticos no son uniformes.…”
Section: Traducción De Los Títulosunclassified